Fabrication of Highly Porous Alumina-Based Ceramics with Connected Spaces by Employing PMMA Microspheres as a Template - Kazutaka Kamitani; Takeo Hyodo; Yasuhiro Shimizu; Makoto Egashira (Advances in Materials Science and Engineering)
Highly porous alumina-based ceramics were fabricated by a slip casting method by employing polymethylmethacrylate (PMMA) microspheres having different diameters as a template and MgO or SiC powder as a sintering aid and subsequent calcination at 1600∘C. Spherical pores reflecting the morphology of the PMMA microspheres could be fabricated. In addition, the formation of much smaller connected space among the pores was observed on the pore's inner walls of all ceramics. In this method, porous structure, for example, pore diameter, shape (open or closed), and mechanical properties, could be controlled by varying the particle size of PMMA microspheres and its concentration in alumina-based slurries. Highly porous and mechanically strong alumina-based ceramics having an open porosity of 62%, a connected space size of 1.3 𝜇m, and a compressive strength of 147.6 MPa could be fabricated by employing PMMA microspheres with a mean particle size of 22.6 𝜇m and an appropriate amount of SiC.